Design of Integrated Science Learning Materials Based on Creative Problem Solving Model Integrated with Anti-Corruption Characters - Widya Widya; Ena Suma Indrawati; Desy Eka Muliani; Mila Ridhatullah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2019)
The 2013 curriculum requires student-centered learning. The teacher as a facilitator needs to prepare student-centered learning. The teacher prepares learning that emphasizes the thought process. Creative Problem Solving (CPS) models can develop students' thinking abilities. Teachers are expected to be able to develop teaching materials that are appropriate to the character of students. Teaching materials developed improve students' thinking skills. Teaching materials provided should also be able to increase student awareness of the nation's problems. One of Indonesia's big problems is corruption. Learning in schools is expected to instill anti-corruption character, one of which is integrating learning. This research is research and development. In this article is a part of the design of the teaching material that was developed. The data collection technique used is a prototype review of teaching materials developed. Analysis of the data used descriptive analysis. The results of this study are in the form of instructional material design based on the CPS model. The science teaching materials developed are based on the syntax of the CPS which consists of: identifying objectives, collecting data, sharpening questions, collecting data, formulating solutions, and implementing solutions. In addition to the teaching material developed it is also integrated with the anti-corruption character in each step of the problem solving that is displayed.